REKONDISI MESIN BUBUT KRISBOW BU24 DI LABORATORIUM PEMESINAN DASAR POLITEKNIK MANUFAKTUR NEGERI BANGKA BELITUNG - Mirza Hadistiya; Yogi Saipullah; Fajar Aswin; Muhammad Rivai (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Lathe machine is one of machines that used as a medium for the production and learning process at the Bangka Belitung State Manufacturing Polytechnic. Due to the impact of the time, some lathes experiencing a reduction in both of function and condition,such as the Krisbow BU24 lathe machine which has some troubles such as a gearbox, a longitudinal carriage, coolant system, and emergency button as of needed an recondition action in order to the lathe machine condition is acceptable. In the recondition process there some acts such as machine observation, technician interview, literature studies,and initial testing. Then, did a troubles analysis from the datas, the plan of maintenance that obtaining a maintenance schedule and spare parts procurement. After that, the process of recondition and testing which include a function test, performance test, and geometrical test. After the reconditioning process for the Krisbow BU24 lathe machine is expected to be in an acceptable condition.